2015
DOI: 10.1002/2015gl064089
|View full text |Cite
|
Sign up to set email alerts
|

Coherent water transport across the South Atlantic

Abstract: The role of mesoscale eddies in transporting Agulhas leakage is investigated using a recent technique from nonlinear dynamical systems theory applied on geostrophic currents inferred from the over two decade long satellite altimetry record. Eddies are found to acquire material coherence away from the Agulhas retroflection, near the Walvis Ridge in the South Atlantic. Yearly, one to four coherent material eddies are detected with diameters ranging from 40 to 280 km. A total of 23 eddy cores of about 50 km in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(102 citation statements)
references
References 36 publications
9
91
0
2
Order By: Relevance
“…However, it is still possible that more realistic flows, such as our double-gyre flow and real ocean circulations, contain vortices that straddle zonal jets and thus only partly contribute to striations. The estimate of eddy contribution to the striations depends on the method of identifying eddy boundaries, which is a challenging task (e.g., Beron-Vera et al 2013;Wu 2014;Faghmous et al 2015;Wang et al 2015). For example, Buckingham and Cornillon (2013) showed that eddies detected by a contour identification method account for 30%-70% of the velocity variance of striations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still possible that more realistic flows, such as our double-gyre flow and real ocean circulations, contain vortices that straddle zonal jets and thus only partly contribute to striations. The estimate of eddy contribution to the striations depends on the method of identifying eddy boundaries, which is a challenging task (e.g., Beron-Vera et al 2013;Wu 2014;Faghmous et al 2015;Wang et al 2015). For example, Buckingham and Cornillon (2013) showed that eddies detected by a contour identification method account for 30%-70% of the velocity variance of striations.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2a shows a cross section of an anticyclonic Gaussian eddy, and the corresponding E 2 parameter; this parameter is nonzero only within the vortex core, which overlaps the vortex part circled by the extremum of the rotational speed. This E 2 parameter is based on rotation and fluid deformation, unlike some other techniques that emphasize eddy material transport (e.g., Beron-Vera et al 2013;Wang et al 2015). A comparison of different methods on identifying mesoscale eddies can be found in Faghmous et al (2015).…”
Section: Detection Of the Cores Of Coherent Eddiesmentioning
confidence: 99%
“…Using different eddy detection methods, several authors have attempted to reconstruct and analyze Agulhas Rings trajectories in and across the South Atlantic (e.g., Byrne et al, ; Gordon & Haxby, ; Souza, de Boyer Montégut, Cabanes, & Klein, ; Wang et al, ). In the published studies, most reconstructions of the trajectories of Agulhas Rings leaving the Cape Basin are identified initially well within the Cape Basin and not at the Agulhas Current Retroflection where they are believed to originate (e.g., Byrne et al, ; Guerra et al, ; Souza, de Boyer Montégut, Cabanes, & Klein, ; Wang et al, , ). Taking into account the separation of an eddy into smaller structures, to which, in what follows, we will refer to as an eddy splitting event, Dencausse et al () tracked the Agulhas Rings formed in the Agulhas Retroflection area and entering the Cape Basin.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout their lifespan, eddies generally stretch and undergo filamentation causing dispersion of the fluid mass (Beron‐Vera et al, ; Haller & Beron‐Vera, ); thus, the potential of eddies to affect their environment through the retention and transport of water is not well known. Theoretical and modeling studies have examined the dynamics of retention and leakage by eddies (e.g., de Steur & van Leeuwen, ; Early et al, ; Froyland et al, ; Haller, ), and a few studies have identified water mass transport based on Lagrangian eddy boundaries (Beron‐Vera et al, , ; Wang et al, ). However, a systematic characterization of retention by mesoscale eddies has rarely been attempted (but see Abernathey & Haller, ).…”
Section: Introductionmentioning
confidence: 99%